Psycholinguistics of AI, Psycholinguistics versus Machine code - Coulardeau, Jacques (Signo, 2022)
I will examine the background of the language phylogeny in emerging Homo Sapiens as a fast, bipedal, long-distance runner in Black Africa;, followed by language psychogenesis in children from their gestation twenty-fourth week onward. I will concentrate on the audio-visual machiness impact,  Lacan’s mirror stage,  AV machines, the discontinuity between real and virtual realities, the remote control and AI machines as smart speakers and smart homes.  In addition, I will discuss the following questions: Is the Machine beyond human intelligence? Is the human individual beyond Homo Sapiens? Is the human community beyond social contract? My working hypotheses on education within phylogenetic psycholinguistics are built on the following topics: Tomorrow’s AI class (unit and room); guided self-learning and who is the guide; can transference and countertransference take place in AI-guided self-learning? Can a human subject develop such transference/countertransference with a machine? Can a machine “play the game”? In conclusion, I will debate “The utopian vision of an improved human being versus the dystopic vision of human beings and human communities totally enslaved to AI machines. Keywords: AI; linguistic phylogeny; guided self-learning; (counter)-transference; enslaved-to-machines